S Strategi Pemanfaatan Limbah Padat Kelapa Sawit Di Provinsi Jambi - HARKENI, ASTI HARKENI (Brida Provinsi Jambi, 2024)
The potential for oil palm plantations in Jambi Province is very large. The vast area of oil palm land besides having the potential also causes its own problems. The side effects caused are the abundance of solid waste produced by palm oil in the form of fronds, stems, empty bunches, leaves and sticks. The abundance of solid palm oil waste is a problem in itself, especially for the environment. Through this research, it will be analyzed how the use of palm oil waste in community-owned oil palm plantation areas so that it can provide additional income for the community. This research uses a descriptive approach with mixed methods (combined qualitative and quantitative research) using AHP (Analysis Hierarchy Process) analysis tools is a decision-making method by simplifying a complex problem that is unstructured, strategic and dynamic in the form of a hierarchy. The results showed that an alternative innovation in solid waste treatment technology that is environmentally friendly is an alternative with the best weight of 0.425 and this is the first alternative ranking that can be done. Meanwhile, in the second order that can be done is the development of regulations with a weight of 0.232. In addition, the third alternative that has a weight of 0.220 is the support of private parties / palm oil companies and the last is socialization for oil palm farming communities with a weight of 0.123.